1997
DOI: 10.1074/jbc.272.33.20782
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Expression of a New Water Channel Abundantly Expressed in the Testis Permeable to Water, Glycerol, and Urea

Abstract: A new member of the aquaporin (AQP) family has been identified from rat testis. This gene, referred as aquaporin 7 (AQP7), encodes a 269-amino acid protein that contained the conserved NPA motifs of MIP family proteins. AQP7 has the amino acid sequence homology with other aquaporins (ϳ30%), and it is highest with AQP3 (48%), suggesting that both AQP3 and AQP7 belong to a subfamily in the MIP family. Injection of AQP7-cRNA into Xenopus oocytes expressed a 26-kDa protein detected by immunoblotting. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
245
0
7

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 358 publications
(263 citation statements)
references
References 19 publications
11
245
0
7
Order By: Relevance
“…AQP7 is an aquaglyceroporin that is abundantly expressed in kidney, testis, and adipocytes (6,9). Moreover, AQP7 is also known to allow rapid urea and arsenite transport (6,12). In the kidney, AQP7 is expressed on the apical membrane of the proximal straight tubules (S3 segment) (6), where AQP1 is also present (19).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…AQP7 is an aquaglyceroporin that is abundantly expressed in kidney, testis, and adipocytes (6,9). Moreover, AQP7 is also known to allow rapid urea and arsenite transport (6,12). In the kidney, AQP7 is expressed on the apical membrane of the proximal straight tubules (S3 segment) (6), where AQP1 is also present (19).…”
mentioning
confidence: 99%
“…Moreover, AQP7 is also known to allow rapid urea and arsenite transport (6,12). In the kidney, AQP7 is expressed on the apical membrane of the proximal straight tubules (S3 segment) (6), where AQP1 is also present (19). Studies of AQP1 knockout mice have shown that AQP1 plays a major role in proximal tubular water transport (15,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As it was cloned and identified first in the rat testis [59], reports on AQP7 on germ cells and spermatozoa have been most consistent among AQPs ( Table 1). The diffuse staining of the cytoplasm, in addition to the plasma membrane (also for AQP8), may represent the degraded protein in view of the dynamic formation and differentiation of spermatids ( Figure 1A and B).…”
Section: Aqp7mentioning
confidence: 94%
“…Recently, it was proposed that aquaporins might be active players in sperm volume-regulatory water fl ux [11] . Indeed, two aquaporins (AQP7 and 8) were fi rst cloned from rat testes and identifi ed by staining in murine sperm tails [12][13][14] . Aquaporin-11 (AQP11) has also been found in the end piece of rat sperm [15] (although some controversies exist due to variable antibody specifi city; for a more detailed description, see the comprehensive review [14] ).…”
Section: Efficient Sperm Volume Regulation Is a Prerequisite For Normmentioning
confidence: 99%